Extreme performance of multi-layer laminated glass designs under blast loads - Andrew Bowman; Alaa El-Sisi; Ahmed Elbelbisi; Ahmed Elkilani; Hesham Elemam; Hani Salim (Scientific Reports)
Abstract Laminated Glass (LG) is a safety glass made by bonding multiple glass layers together with a polymeric interlayer, offering protection against flying shards, especially in explosive scenarios. In this paper, a numerical study was performed to study the effect of the laminated glass cross-section on the blast performance of the panel. Different configurations were studied, such as a double glass layer with interlayers, a double glass layer with hybrid interlayers, and a variety of multi-glass layer configurations with interlayers. Variations of glass layer thicknesses, number of glass layers, and order of glass layers were studied to evaluate the optimal design of the LG panel. Four different polymer interlayers were considered in this analysis: polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU), and the ionomer SentryGlas® (SG). A high-fidelity numerical model, capable of capturing damage and fracture of the LG, was employed using the Arbitrary Lagrangian–Eulerian three-dimensional analysis (ALE3D) multiphysics software, and blast load simulations were developed and verified against experimental data from the literature. Results show that interlayer type affects blast resistance differently, with EVA panels exhibiting the highest deformation and SG panels the least, indicating higher strength and better performance in SG interlayer panels. Increasing interlayer thickness enhances LG panel resistance in the pre-cracked stage. It was found that SG performs better than PVB and much better than TPU/EVA. EVA and TPU performed poorly and completely tore under the used blast loading. Hybrid interlayers underperformed, possibly due to unbalanced load sharing between the stiffer middle interlayer and the more compliant EVA outer membrane. Finally, unique combinations of glass thicknesses and configurations were studied and indicate that LG systems with a thick middle layer and thin outer layers deflect the least during a blast load. These findings underscore the critical role of layup design in enhancing the blast resistance of multi-layer LG panels.